2018
DOI: 10.1002/jaba.511
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing influence of arbitrarily applicable verbal relations of recreational gamblers: A randomized controlled trial

Abstract: Twenty‐one recreational gamblers were randomly assigned to two groups; one group was exposed to a conditional discrimination relational training task to bias choice allocation to a black machine presented concurrently with a red machine, and the other group underwent the same relational training task immediately followed by a defusion procedure, designed to expand upon the relations developed in the initial relational task. Both groups completed a simulated slot‐machine task before and after the relational tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Previous findings indicate that the near-miss effect in simulated slot-machine gambling may be altered through verbal relations (Belisle et al, 2019;M. R. Dixon et al, 2011;Dymond et al, 2012) but only when win, near-miss, and loss outcome reel displays are related to the written text "win," "loss," and "almost."…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous findings indicate that the near-miss effect in simulated slot-machine gambling may be altered through verbal relations (Belisle et al, 2019;M. R. Dixon et al, 2011;Dymond et al, 2012) but only when win, near-miss, and loss outcome reel displays are related to the written text "win," "loss," and "almost."…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings indicate that the near-miss effect in simulated slot-machine gambling may be altered through verbal relations (Belisle et al, 2019; M. R. Dixon et al, 2011; Dymond et al, 2012) but only when win, near-miss, and loss outcome reel displays are related to the written text “win,” “loss,” and “almost.” Our findings show that gambling-specific stimuli commonly associated with slot machines may acquire symbolic properties of same and opposite which then exert a subsequent influence over win expectancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As well as enhancing the validity of laboratory-based treatment studies, this approach has the potential to better inform treatment approaches aimed at reducing the frequency of problematic slot-machine gambling rather than eradicating it entirely (Dickerson & Weeks, 1979;Ladouceur, Lachance, & Fournier, 2009). Belisle, Paliliunas, Dixon, and Speelman (2018) demonstrated that the effects of a non-arbitrary relational training task on slot machine choice could subsequently be reduced Symbolic generalization 20 through using defusion techniques derived from therapeutic exercises (Assaz, Roche, Kanter, & Oshiro, 2018). Defusion involves altering the way an individual relates to their thoughts and aims to modify undesirable functions of language.…”
Section: Discussionmentioning
confidence: 99%